2008
DOI: 10.1007/bf03033502
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neuromotor functions in hospital laboratory workers exposed to low levels of organic solvents

Abstract: Solvents are ubiquitous in industrial societies in a wide range of processes, and long-term exposure to these organic compounds may impair neuromotor functions such as equilibrium function. However, there is limited knowledge of effects on posture and gaze control after organic solvent exposures below workplace threshold limit values. The aim of this study was to evaluate the consequences of low-level co-exposure to organic solvents on balance and gaze control in hospital laboratory workers. Twelve hospital la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Few studies investigated effects of chronic exposure to volatile organic solvents on balance control through posturography, which is now recognized as a useful technique to assess neurotoxic effects on CNS (Ledin et al 1991;Kuo et al 1996;Yokoyama et al 1997;Iwata et al 2005;Vouriot et al 2005b;Herpin et al 2008). While most studies have shown that chronic exposure close to or higher than workplace threshold limit values led to balance disorders, the additive neurotoxic effects after a weeklong exposure, defined here as subchronic, are, to our knowledge, less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies investigated effects of chronic exposure to volatile organic solvents on balance control through posturography, which is now recognized as a useful technique to assess neurotoxic effects on CNS (Ledin et al 1991;Kuo et al 1996;Yokoyama et al 1997;Iwata et al 2005;Vouriot et al 2005b;Herpin et al 2008). While most studies have shown that chronic exposure close to or higher than workplace threshold limit values led to balance disorders, the additive neurotoxic effects after a weeklong exposure, defined here as subchronic, are, to our knowledge, less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of chloroform may require attention 4,14,15,23) because this solvent is commonly used in laboratories but only on rare occasions on production floors ( Table 1). The descriptions of solvent application in histology laboratories would be expected to be simple 16,17,21,22) because xylenes, toluene or the combination of them would be the only solvents used in this field of study 6) . Overall, therefore, it was not possible to examine if the observations as summarized in Table 1 could be confirmed through a literature survey.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, use of xylenes in histology laboratories were reported by Gunson et al [6] and Purdie et al [8], suggesting that xylenes are commonly used in histopathology laboratories in medical fields, as in the present cases (Table 4). In addition, Herpin et al [7] reported that laboratory technicians in charge of 'anatomy sample preparation for microscopic analysis' were exposed to toluene and ethyl alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, information on the solvent use has been reported only on limited occasions and usually as a simple compilation of solvent names [5][6][7][8][9][10] with no further details such as use prevalence. In the present study, seven large research institutions were studied for solvent use in laboratories.…”
Section: Introductionmentioning
confidence: 99%